Selfies as self-representation tools during the construction of narrative identities - Mokwala, Precious (University of the Free State, 2020)
In this study, the topic of selfies as tools for self-representation during the construction of narrative identity is explored. Emerging adulthood, narrative identity and selfies were the focus of the study. Emerging adulthood is a dynamic developmental stage in which the main developmental task is the exploration of identity, particularly in western societies. It was, therefore, important to examine this life stage as it is experienced by emerging adults in the South African context, but with a story-telling aspect. The social constructivist perspective as a theoretical framework was adopted for this study, as it indicates that several elements – including but not limited to family, peers, friends, media, religion and culture – ultimately affect narrative identity development. A qualitative framework was employed to explore the participants’ narratives. Narrative identity is socially constructed and develops through interaction with others, and meaning-making is also part of the process. Data collection took the form of four focus groups, with a group total of twenty-five, consisting of diverse participants who had been sampled by means of purposive and snowball sampling. Data were analysed using thematic analysis in which extensive coding was done, and themes were constructed by analysing the participants’ responses. Emerging adults narrate their life stories in accordance with their personal preferences but also in accordance with external standards that have been stipulated by the societies in which they exist. Life stories were expressed through selfies, in which communication has evolved from the textual to the visual. Some similarities were identified between the experiences of emerging adults in western societies and those in African societies. The limitations of this research study were identified, and these will hopefully be valuable for future studies in this area.
Dissertation (M.Soc.Sc. (Clinical Psychology))--University of the Free State, 2020
Keywords: Emerging adulthood; Narrative identity; Identity exploration; Social media; Selfies; Sociocultural; South Africa